PENGARUH PELATIHAN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PT PERTAMINA PATRA NIAGA FUEL TERMINAL BANDUNG GROUP UJUNG BERUNG - Eva Hamami; Syarifuddin Syarifuddin (Universitas Bina Taruna Gorontalo, 2024)
This research aims to find out the impact of work training and physical work environment on the performance of employees of PT Pertamina Patra Niaga Fuel Terminal Bandung Group Ujung Berung.This research uses a method of quantitative approach, and this type of research is a causality descriptive study. The sampling techniques used are nonprobality samplings and saturated samples with respondents of 30 employees. Descriptive analysis and double linear analysis are used to analyze data.Employee performance is very important in a company because it is the primary basis that determines success in achieving the goals of the Company. Employees performance is influenced by several factors including the competence of employees and the organizational environment. The results of the analysis showed that job training belonged to the category